Blood–Brain Barrier Dysfunction, Edema Formation and Functional Recovery in Ischemic and Hemorrhagic Stroke: A Retrospective Study - Müller, Christian; Sembill, Jochen; Kallmünzer, Bernd; Bailer, Maximilian; Singer, Ludwig; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Balk, Stefanie; Sprügel, Maximilian (Neurology International, 2025)
Objectives: We aimed to determine temporal patterns of blood–brain barrier (BBB) dysfunction, edema formation and functional recovery in acute stroke. Materials and Methods: Patients of two observational studies on ischemic and hemorrhagic stroke between 2006 and 2019 were analyzed. Blood–brain barrier dysfunction was assessed using the cerebrospinal fluid-to-plasma albumin ratio. Edema formation was measured on all available imaging scans during hospital stay. Relative edema was defined as the ratio of edema volume to stroke volume. Multivariable regression models were applied to analyze associations and calculate predicted probabilities. Results: Overall, 138 stroke patients, 103 (74.6%) with ischemic stroke and 35 (25.4%) with hemorrhagic stroke, were analyzed. The predicted probability of substantial BBB dysfunction was approximately 46 (37–55) % among patients analyzed on 1 day after symptom onset and declined with increasing time, thereafter reaching 10 (3–29) % on day 30. The maximal extent of edema was lower in ischemic versus hemorrhagic stroke (relative edema: 1.5 [1.2–1.8] vs. 2.6 [1.9–4.5], p = 0.003) and occurred earlier after stroke onset (5.9 [4.6–8.5] days vs. 12.3 [9.7–16.4] days, p = 0.009). BBB dysfunction was associated with increased edema formation (adjusted relative edema: 4.0 [2.8–4.5] vs. 2.3 [1.8–3.0], p = 0.037) and lower chances of functional recovery (20/48 [41.7%] vs. 51/90 [56.7%], adjusted Odds Ratio: 0.37 [0.16–0.88], p = 0.025) in both ischemic and hemorrhagic stroke patients. Conclusions: BBB dysfunction frequently occurred in acute ischemic and hemorrhagic stroke and was associated with secondary injury and worse clinical outcomes. Future studies should evaluate BBB dysfunction as a potential therapeutic target using advanced imaging techniques early after stroke onset. Edema formation was aggravated and prolonged in hemorrhagic versus ischemic stroke.
CRIS-Team Scopus Importer:2025-12-12
Keywords: blood–brain barrier; cerebral edema; function recovery; intracerebral hemorrhage; stroke